Translation of the Fugl-Meyer assessment into Romanian: Transcultural and semantic-linguistic adaptations and clinical validation - Onose, Gelu; Anghelescu, Aurelian; Ionescu, Anca; Tataranu, Ligia Gabriela; Spînu, Aura; Bumbea, Ana Maria; Toader, Corneliu; Tuţă, Sorin; Carare, Roxana O.; Popescu, Cristina; Munteanu, Constantin, Collaborative Working Group; et al. (Frontiers in Neurology, 2023)
Stroke, considering, on one hand, its frequency - especially in a globally aging population - and on the other, its devastating consequences: high life-threatening risk or severe long-term disability, is a major public health problem. An appropriate tool for evaluating post-stroke sensory-motor and other somatic, possible deficits, largely used and highly recommended, is the Fugl-Meyer Assessment (FMA) scale. Methods. We have completed a standardized procedure for the: translation, transcultural and semantic-linguistic adaptation into Romanian of the FMA’s afferent evaluation official protocols, for both, upper and lower extremities, through three main steps. For the related clinical validation, we evaluated 10 post-stroke patients, two times. Results. Svensson’s method confirmed overall good inter-rater and intra-rater results for the main parts of the Final Romanian version of the FMA’s evaluation protocols, regarding the: percent of agreement (≥ 80% on average), and for disagreement: relative position (values outside the interval of [-0.1, 0.1] in only 2 measurements out of the 56 comparisons we did), relative concentration (values outside the interval of [-0.1, 0.1] in only 9 measurements out of the same 56 comparisons done), and relative rank variation (all values within the interval of [0, 0.1] in only 5 measurements out of the same 56 comparisons done). High correlation values were obtained between the Final Romanian version of the FMA’s evaluation protocols and the Barthel Index (rho=0.9167; p=0.0002) for FMA Upper Extremity Total A-D (motor function) and rho=0,6319, and p=0,0499 for FMA Lower Extremity Total E-F (motor function), and close to limit, with the modified Rankin Scale (rho= -0.5937; p=0.0704) for FMA Upper Extremity Total A-D (motor function)and (rho= -0.6615; p=0.0372) for FMA Lower Extremity Total E-F (motor function) Conclusions. The Final Romanian version of the FMA’s evaluation official protocols showed good preliminary reliability and validity, which can be thus recommended to be used and hopefully will help to a better, standardized, avail of this assessment scale for post-stroke patients in Romania. This endeavor could be added to similar international translation and cross-cultural adaptation achievements, thereby facilitating a more appropriate comparison of the evaluation and outcomes in the management of stroke world-wide.